A New Nano Adjuvant of PF3 Used for an Enhanced Hepatitis B Vaccine - Shan, Pu; Wang, Zhibiao; Li, Jilai; Wei, Duoqian; Zhang, Zhuan; Hao, Shaojie; Hou, Yibo; Wang, Yunyang; Li, Shuxiang; Wang, Xudong; Xu, Jing (Frontiers in Bioengineering and Biotechnology, 2022)
Recombinant protein vaccines, with highly pure ingredients and good safety, are gradually replacing some attenuated and inactivated vaccines in clinical practice. However, since of their low immunogenicity of the recombinant proteins, adjuvants are often needed to enhance immune response after vaccination. Aluminum adjuvant is widely used in some vaccines for decades, it can induce strong humoral immunity, but the deficiency of cellular immunity limits its application for some vaccines. Therefore, it is urgently needed to develop novel adjuvant to increase not only humoral but also cellular immune response. To address this, we designed and prepared a new nano adjuvant (PF3) through microfluidization by the combination of saponin (Ginsenoside Rg1) and oil-in-water nano emulsion (NE) in the present study. As compared to aluminum adjuvant, PF3 had stronger humoral and cellular immune induction effect because of high cellular uptake and activization of immune response pathways. Furthermore, PF3 showed better immune enhancement and acceptable biosafety equivalent to that of aluminum adjuvant. In addition, no obvious changes of PF3 were observed in size and zeta potential after 12 weeks storage at 4℃ and 37℃, demonstrating its high stability in vitro. This study provided an adjuvant platform to replace traditional aluminum adjuvant in design of recombinant vaccines.